Effect of A‐site atom on static corrosion behavior and irradiation damage of Ti2SC phases. Issue 2 (20th October 2021) - Chen, Ke; Wang, Xudong; Zhang, Jianning; Ding, Haoming; Li, Youbing; Song, Yujie; Ge, Fangfang; Zhou, Xiaobing; Du, Shiyu; Huang, Qing
Abstract: MAX phases are a large family of damage‐tolerant structural materials for the nuclear energy industry. The anti‐corrosive property to the tritium fluoride (TF) produced by the neutron irradiation of FLiBe is an issue for the MAX phases applied to the molten salt reactors (MSRs). Herein, the Ti2 SC phase was used for the first time to evaluate the corrosion resistance to the concentrated hydrofluoric acid as the simulated service condition. The comprehensive characterizations including weight‐loss curves, X‐ray diffraction, field emission scanning electron microscopy, and energy dispersive spectroscopy were employed to analyze the corrosion behavior and mechanism of Ti2 SC in comparison with Ti3 AlC2 and Ti3 SiC2 . The good intrinsic anti‐corrosive property of Ti2 SC was originated from the strong Ti‐S bond. Considering the acceptable preliminary performance at low displacement per atom (dpa), the Ti2 SC probably has a potential to be used as the structural material in the MSRs.